Entwurf und Leistungsbewertung von Ad-hoc-Kommunikationsnetzen für den Katastrophenschutz - Wolff, Andreas Herbert (Technische Universität Dortmund, 2013)
A reliable communications network provides the essential basis for future IT-based services for rescue personnel at an incident scene. Nowadays, the communication in civil protection is based on the digital trunked radio TETRA system, or is still based on analog BOS radio system. These systems do not provide sufficient data rate for multimedia applications. Existing infrastructure networks, such as the public mobile telephony network, can be damaged in a major incident situation and therefore are not fully usable for rescue personnel. To use new multimedia services at the incident scene, rescue personnel therefore dependent on their own local communications network. For the rescue personnel a practicable network deployment is essential, whereas the technology should not hinder the rescue process. Moreover, there are demands on the quality of service of the network, and the performance in terms of the data rate, as for example videos should be transferred from helmet cameras. The aim of this thesis is the design and performance evaluation of a robust communications solution for ad hoc networks in disaster management. To enable a user-friendly network deployment, a reliable networking approach is presented which allows a selfconfiguring ad hoc deployment. Working closely with the fire department, rescue processcompliant network deployment strategies are investigated which can be used as a basis for reliable communication. The key enabling technology of the approach is Wi-Fi communication, which operates in 5GHz band. WLAN stations of one network can interfere with each other or can be interfered by other networks on the same channel. In this work, a method for reducing the interference is introduced. The proposed Interference Avoidance Algorithm (IAA) disables redundant router in the network of rescue personnel. It can be shown by simulations that on average in the investigated scenarios a higher packet delivery ratio can be achieved when IAA is active compared to networks without IAA. In order to reduce interference caused by other networks, a prioritization of the communication of the rescue personnel with the introduction of new communication classes is proposed. This concept is based on the modification of the parameters of the medium access function (DCF) of wireless LAN, which is comparable with IEEE 802.11e but is more prioritized, and is called Emergency-DCF. For its performance evaluation, an existing Markov model is modified and extended. Then, the analytical results are validated by simulation. The feasibility of the method can be validated experimentally. The presented solutions of this thesis have been developed within and were contributed to research projects, where partners from the industry and end-users were actively involved. Thus, the network concept developed within this thesis was tested together with the Dortmund fire brigades during the project MobileEmerGIS. Moreover, the process oriented networking was validated during field tests by Gelsenkirchen fire brigade during the BMBF project SPIDER. The networking concept was also used in a modified version for networking the flying robots in the BMBF project Airshield. With several publications in conferences and presentations at workshops, an international resonance has been achieved. Currently, the results of this thesis are being deployed with the German Red Cross in Bavaria.
Keywords: Ad-hoc; Dienstgüte; Katastrophenschutz; WLAN; 620